Robust Estimation and Forecasting of the Capital Asset Pricing Model - Guorui Bian; Michael McAleer; Wing-Keung Wong (Tinbergen Institute, 2013)
In this paper, we develop a modified maximum likelihood (MML) estimator for the multiple linear regression model with underlying student t distribution. We obtain the closed form of the estimators, derive the asymptotic properties, and demonstrate that the MML estimator is more appropriate for estimating the parameters of the Capital Asset Pricing Model by comparing its performance with least squares estimators (LSE) on the monthly returns of US portfolios. The empirical results reveal that the MML estimators are more efficient than LSE in terms of the relative efficiency of one-step-ahead forecast mean square error in small samples
urn:NBN:nl:ui:15-1765/39186
Keywords: C1; C2; G1; 330; Maximum likelihood estimators; Modified maximum likelihood estimators; Student t family; Capital asset pricing model; Robustness; Maximum-Likelihood-Methode; CAPM; Robustes Verfahren; Theorie